The principles of cascading power limits in small, fast biological and engineered systems - Ilton, Mark; Saad Bhamla, M.; Ma, Xiaotian; Cox, Suzanne M.; Fitchett, Leah L.; Kim, Yongjin; Koh, Je sung; Krishnamurthy, Deepak; Kuo, Chi Yun; Temel, Fatma Zeynep; Crosby, Alfred J.; Prakash, Manu; et al. (Science, 2018)
Mechanical power limitations emerge from the physical trade-off between force and velocity. Many biological systems incorporate power-enhancing mechanisms enabling extraordinary accelerations at small sizes. We establish how power enhancement emerges through the dynamic coupling of motors, springs, and latches and reveal how each displays its own force-velocity behavior. We mathematically demonstrate a tunable performance space for spring-actuated movement that is applicable to biological and synthetic systems. Incorporating nonideal spring behavior and parameterizing latch dynamics allows the identification of critical transitions in mass and trade-offs in spring scaling, both of which offer explanations for long-observed scaling patterns in biological systems. This analysis defines the cascading challenges of power enhancement, explores their emergent effects in biological and engineered systems, and charts a pathway for higher-level analysis and synthesis of power-amplified systems.
Keywords: Biomechanical Phenomena; Models, Theoretical